Promising forage resources for production systems in Mediterranean areas - Pecetti L.; Annicchiarico P.; Porqueddu C.; Melis R.A.M.; Thami Alami I.; Bouizgaren A.; Laouar M.; Abdelguerfi A.; Abbas K.; Hayek T.; Julier B. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Extensive livestock production is a basic socio-economic feature of Mediterranean agriculture threatened by overgrazing of natural grasslands and by climate change. Stress-tolerant forage resources are increasingly needed, therefore, to enhance the sustainability of Mediterranean crop-livestock systems. Assessing the response of the available germplasm of a few, key species across different stress levels of the Mediterranean area can provide information on best plant types, genetic resources and adaptation strategies. A large set of experiments (here summarised) was performed for over a decade on both sides of the western Mediterranean basin, indicating that germplasm adapted to dryland conditions can be found in all forage species. This germplasm could be directly used for cropping or as parental material in breeding programmes. A clear genotype × environment interaction was generally found for yield, emphasising the need of selecting specific germplasm for different environments. Legume-based crops displayed higher forage quality and farmers’ appreciation than pure-stand crops of cereals or grasses.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)